Efficient accelerated simulation technique for packet switched networks : a buffer with two priority inputs - Ariffin, Sharifah H. S.; Schormans, John A. (IEEE, 2004)
An Enhanced Traffic Aggregation (E_TA) technique for acceleration simulation of packet switched network is proposed. This technique simplifies the simulation model and improves the efficiency by using packet-train or packet rate source traffic with non FIFO scheduler in the buffer. The model employs power law traffic which recently proved to be able to capture both long-range dependence and the burstiness of aggregate broadband network traffic. Our results show that using E_TA with FIFO scheduler simulation times can be reduced by 39%, and using E_TA with non FIFO scheduler by 83 %.